The Port of Ende as a Feeder Point in Indonesia’s Maritime Trade Network in the 20th Century - amaira azizah; Faris Sauqi Syahid; Abd Rahman Hamid; Agus Mahfuddin Setiawan (Criksetra: Jurnal Pendidikan Sejarah, 2026)
This paper examines the role of Ende Port on Flores Island as a navigational reference point and strategic transit port within the eastern Indonesian shipping network from the nineteenth century to the early years of independence. Using a historical approach, this study shows how Ende's location on the southern coast of Flores, facing the Sawu Sea, made it a natural confirmation point for sailors travelling from Bali toward Timor and Maluku. Beyond guiding traditional navigation through stars, monsoon winds, and coastal landmarks, Ende also offered a sheltered harbor for resupply and for waiting out unfavorable weather. The paper further traces the shipping network linking Ende with the major Balinese ports of Singaraja and Benoa, the principal gateways to eastern Indonesia, and shows how the rhythm of ship arrivals at Ende reflected the monsoon system, the Dutch colonial presence, and the port's integration into the KPM shipping route in 1891. Although Ende produced no major export commodity of its own, it played an essential role in sustaining the flow of trade and shipping across the archipelago. The study contributes to Indonesian maritime historiography by highlighting the strategic function of small ports long overlooked in the traditional maritime trade system.